Cross‐sectional Evaluation of Home Enteral Nutrition Practice in the United States in the Context of the New Enteral Connectors. Issue 8 (7th February 2019) - Epp, Lisa M.; Salonen, Bradley R.; Hurt, Ryan T.; Mundi, Manpreet S.
Abstract: Purpose: The increased prevalence of home enteral nutrition (HEN), reemergence of blenderized tube feeding (BTF), and conversion of enteral connectors to the ISO 80369‐3 standard are creating a significant need to better understand the practices of the HEN population. A cross‐sectional survey of current HEN consumers was conducted to evaluate the demographics of HEN consumers, including formulas and feeding tubes being used. Methods: In order to disseminate the survey to a wide range of HEN consumers, we partnered with private infusion companies (Coram and Pediatric Home Services) along with the Oley and Tube Feeding Awareness Foundations. A validated survey focusing on patient demographics, tube types, formula used, and tube clogging complications was placed online from September 1, 2016, to October 15, 2016. Results: During the study period, 1519 surveys were completed, with 1062 respondents in the pediatric group (<18 years old) and 457 in the adult group (≥18 years old). The most popular formulas were standard polymeric and specialized formulas in both the pediatric and adult groups. However, a significant number in the pediatric (31.2%) and adult (18.6%) groups used BTF either alone or in combination with other formulas. Clogging was also quite prevalent and correlated with tube size. Conclusions: The present study highlights the significant diversity of the HEN practice in terms of types and sizes of tubes as well as formulas used, including confirmation of the widespread use of BTF. These data are key to ensure HEN providers are able to appropriately support and educate their patients.